Sustainability Analysis of Business Community Mentoring and Training Program to Increase the Business Scale of its Members - Gunawan Gunawan; Luki Adiati Pratomo (Journal of Social Research, 2023)
The SDGs (Sustainable Development Goals) have 169 targets, 319 indicators, and 17 goals starting from 2015 to 2030. Of the 17 sustainable development goals, one of the SDGs (Sustainable Development Goals) that has received the most attention to date is poverty. This is because all of the SDG’s goals are a form of encouragement and effort to achieve the target of "without poverty" in 2030. Through this research, it is hoped that one can understand the implementation of the SDGs (Sustainable Development Goals) in Jakarta. SDGs (Sustainable Development Goals) can be carried out through the Small Business Community. However, due to the lack of knowledge about global economic developments, assistance is needed. Therefore, the author wants to examine how Sustainability Analysis in the Business Community Program Increases Business Scale. This study used qualitative research methods, data collection was carried out using questionnaires, observation, and documentation. Data analysis techniques use percentages as a basis for interpretation and description to make research results. The results of the study show that the Hands Above business community (TDA Community), JackPreneur, and OKOCE City of Jakarta created mentoring programs to increase business scale. In carrying out the sustainability strategy achieved by MSMEs in Jakarta to maintain and increase business scale, namely in financial governance so that finances remain stable. Business actors carry out promotions in expanding the reach of their businesses so that they can be in demand by the wider community. Business people develop modern business models. The government also encourages business people to develop modern business models, by applying digital technology as a platform in the process of sustaining business community activities to support economic activities in a business continuity strategy.